Conservative versus Invasive Approaches in Temporomandibular Disc Displacement: A Systematic Review of Randomized Controlled Clinical Trials - Manuel Sá; Carlos Faria; Daniel Humberto Pozza (MDPI AG, 2024)
Background: Temporomandibular disorders (TMDs) frequently cause orofacial pain and dysfunction, with treatment options spanning from conservative therapies to invasive surgical procedures. The aim of this systematic review was to analyze and compare the efficacy and safety profiles of conservative, minimally invasive interventions and surgical procedures in patients diagnosed with TMDs and disc displacement. Methods: Following PRISMA recommendations, PubMed, Scopus, and Web of Science databases were searched for randomized clinical trials (RCT). Data were synthesized in a table and evaluated through the Cochrane risk of bias 2 (RoB 2) tool. Results: Thirty-eight RCTs, most with moderate RoB, were selected. Conservative approaches, including physical therapy and occlusal devices, led to an improvement in symptoms and function. Pharmacological treatments demonstrated effectiveness in reducing pain and improving function; however, they can have undesirable side effects. Minimally invasive and invasive treatments also demonstrated efficacy, although most trials did not show their superiority to conservative treatments. Conclusion: The primary approach to TMDs should be a conservative, multimodal treatment plan tailored to patient complaints and characteristics. Treatment goals should focus on symptom control and functional recovery. Surgical treatment should be reserved for cases with a precise diagnosis and a clear etiology.